The search for a more human face for Nelson Mandela: An urgent task - Maluleke, Samuel Tinyiko (HTS teologiese studies, 2015)
For many reasons, reflecting on the life of Nelson Mandela is a precarious exercise. If Mandela is a symbol of the resilience of the human spirit under trying conditions, he is also a symbol that is appropriated in various ways – helpful and unhelpful – by various people. This article explores some of the unhelpful ways in which the name and person of Nelson Mandela is invoked. In particular, the article looks at the hagiographical orientation of several reflections on Mandela, cautioning how some of these may have an effect less noble than originally intended. Accordingly, the article asks: How much can the symbol of Mandela bear? How much more can Mandela give? The logic and rationale of Mandela hagiography is explored. Following his death, there has been an explosion of interest in the life and symbol that is Nelson Mandela. Mandela literature, including multi-media, is on the rise. If the symbol of Mandela is in danger of being ‘cannibalised’, there is also a danger of relegating Mandela to an ahistorical mythical figure. The solution lies in at least two area, namely, the increment of alternative Mandela narratives and the introduction of more critical Mandela narratives. In this regard, Mandela’s own self-understanding as captured in his reflections about his life offer several clues which are explored in this article.